Symmetric dimethylarginine as a biomarker of renal impairment after a decade of follow-up - Hendrik Meyer; Marcus Dörr; Anke Hannemann; Edzard Schwedhelm; Rainer Böger; Till Ittermann; Nele Friedrich; Martin Bahls (Scientific Reports)
Abstract Chronic kidney disease (CKD) is characterized by a gradual and irreversible decline in renal function. Arginine derivatives like symmetric dimethylarginine (SDMA) and asymmetric dimethylarginine (ADMA) have been associated with the progression of renal disease in cross-sectional studies. This study aimed to investigate the longitudinal associations between arginine derivatives and renal function over time in a population-based cohort. Data were derived from the Study of Health in Pomerania-START (SHIP-START-0, n = 3100, mean age 49 years, women 51.3%). The 5-year follow-up included 2174 and the 10-year follow-up 1657 individuals. At baseline, serum concentrations of Arg, ADMA, SDMA and homoarginine were measured using liquid chromatography–tandem mass spectrometry, while renal parameters (creatinine and cystatin C) were quantified at baseline, 5- and 10-year follow-up. Three different statistical analyses (linear regression, logistic regression, analyses of covariance (ANCOVA)), were performed to investigate the longitudinal associations between baseline levels of Arg, ADMA, SMDA and homoarginine as exposure and renal function parameters as outcome. The results showed a significantly inverse longitudinal association between SDMA and renal function. Specifically, a one μmol/l greater SDMA was related to an odds ratio of 1.77 (95% confidence interval (CI) 1.41; 2.21) at 5-year follow-up and 1.43 (95% CI 1.11; 1.84) at 10-year follow-up for kidney dysfunction defined as estimated glomerular filtration rate less than 60 ml/min/1.73 m2. These findings suggest that SDMA might predict future deterioration of renal function. This supports previous findings which suggested that SDMA may be a biomarker for renal function.